THE STATE BUREAU OF INVESTIGATIONS IN THE MODERN SYSTEM LAW ENFORCEMENT BODIES OF UKRAINE: LEGAL ASPECTS OF CREATION AND ACTIVITY - Litvinova, Iryna; Ryepina, Yelizaveta (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to understand the origins of the prerequisites for the creation of the State Bureau of Investigation, to investigate the organizational and legal foundations of the creation and operation of this law enforcement body. Results: the historical basis for the creation of the State Bureau of Investigation has been revealed, since the bureau is a relatively new entity in the law enforcement system of the state, the formation of which continues, and a number of issues need to be specified. The history of regulatory changes that took place on the way to the creation of a legislative framework that is relevant today has been studied. The question was raised regarding the powers of the Director of the State Bureau of Investigation and his duties regarding participation in criminal proceedings. The SBI should become an effective base for the prevention, detection, investigation and termination of crimes, as well as ensure effective countermeasures against corruption that may be committed by senior officials or employees of law enforcement and judicial bodies. After all, the existence of such bodies that can effectively protect the principles of the rule of law and legality and ensure the prosecution and punishment of any person who committed a crime, regardless of his position, status or reputation, is of great importance for the state and the entire society. The State Bureau of Investigation is a law enforcement agency whose activities are aimed at preventing, detecting, stopping, uncovering and investigating crimes within its competence. As well as performing the functions assigned to it, it will also perform a preventive function. Discussion: the establishment of the State Bureau of Investigation is considered a significant step towards European standards and practices of conducting investigations. Under the conditions of perfect management and organization of work, there is a unique opportunity to create a radically new law enforcement agency, which will become a guardian of law and order in the state.